Globally, plant‐soil feedbacks are weak predictors of plant abundance. Issue 4 (27th January 2021) - Reinhart, Kurt O.; Bauer, Jonathan T.; McCarthy‐Neumann, Sarah; MacDougall, Andrew S.; Hierro, José L.; Chiuffo, Mariana C.; Mangan, Scott A.; Heinze, Johannes; Bergmann, Joana; Joshi, Jasmin; Duncan, Richard P.; Diez, Jeff M.; et al.
Abstract: Plant‐soil feedbacks (PSFs) have been shown to strongly affect plant performance under controlled conditions, and PSFs are thought to have far reaching consequences for plant population dynamics and the structuring of plant communities. However, thus far the relationship between PSF and plant species abundance in the field is not consistent. Here, we synthesize PSF experiments from tropical forests to semiarid grasslands, and test for a positive relationship between plant abundance in the field and PSFs estimated from controlled bioassays. We meta‐analyzed results from 22 PSF experiments and found an overall positive correlation (0.12 ≤ r ¯ ≤ 0.32) between plant abundance in the field and PSFs across plant functional types (herbaceous and woody plants) but also variation by plant functional type. Thus, our analysis provides quantitative support that plant abundance has a general albeit weak positive relationship with PSFs across ecosystems. Overall, our results suggest that harmful soil biota tend to accumulate around and disproportionately impact species that are rare. However, data for the herbaceous species, which are most common in the literature, had no significant abundance‐PSFs relationship. Therefore, we conclude that further work is needed within and across biomes, succession stages and plant types, both under controlled and field conditions, while separating PSF effects from other drivers (e.g., herbivory, competition, disturbance) of plant abundance to tease apart the role of soil biota in causing patterns of plant rarity versus commonness. Abstract : Across studies, we detected a small but significant positive correlation between plant‐soil feedbacks measured during controlled experiments and plant field abundance. Plants that are rare are seemingly burdened more by the negative effects of harmful soil biota than common plants.